2023
DOI: 10.3390/pharmaceutics15092306
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Influence of Polyflavonoids from Citrus aurantifolia on Diabetes Treatment and Their Modulation of the PI3K/AKT/FOXO1 Signaling Pathways: Molecular Docking Analyses and In Vivo Investigations

Mohamed A. Hassan,
Ghada M. Abd Elmageed,
Ibtehal G. El-Qazaz
et al.

Abstract: This study was aimed at probing the modulatory influence of polyflavonoids extracted from Citrus aurantifolia, lemon peel extract (LPE-polyflavonoids), on attenuating diabetes mellitus (DM) and its complications. HPLC investigations of the LPE exhibited the incidence of five flavonoids, including diosmin, biochanin A, hesperidin, quercetin, and hesperetin. The in silico impact on ligand-phosphatidylinositol 3-kinase (PI3K) interaction was investigated in terms of polyflavonoid class to explore the non-covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…However, it would be worthwhile for future research to evaluate parameters related to oxidative stress, such as thiobarbituric acid reactive substances (TBARS), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and advanced glycation end-products (AGEs). Moreover, the assessment of inflammatory biomarkers, such as tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), and nuclear factor Kappa B (NF-κB), could also provide valuable insights [69].…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be worthwhile for future research to evaluate parameters related to oxidative stress, such as thiobarbituric acid reactive substances (TBARS), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and advanced glycation end-products (AGEs). Moreover, the assessment of inflammatory biomarkers, such as tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), and nuclear factor Kappa B (NF-κB), could also provide valuable insights [69].…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that FOXO1 may be a key target to quercetin’s effect on glucose signal transduction. The relevant studies have reported that the mediation of FOXO1 by quercetin appears to mainly rely on its upstream genes, such as PI3K, IRS and Akt [ 99 , 100 ]. By inhibiting inflammation, quercetin can modulate the activity of these related genes, thereby influencing FOXO1 regulation.…”
Section: Inflammation Glycometabolism and The Related Signaling Pathwaysmentioning
confidence: 99%
“…Certainly, before organogenesis. that is, 1–7 days, hyperglycemia was, to some extent, reduced [ 242 ]. Hesperidin is a major glycosylated flavonones most commonly present in grapefruit, orange, and lemon fruit.…”
Section: Physiological Threatsmentioning
confidence: 99%